Explore Biomes : Desert Biomes - Gregory, Sarah Wilson (Minneapolis, Minnesota : Kids Core, an imprint of Abdo Publishing, 2023)
"Explore Biomes From dry deserts to tropical rain forests, Earths biomes are home to all kinds of plants and animals. Each biome has a unique climate and can be found in different parts of the planet. Explore Biomes allows readers to discover exciting features about the worlds biomes." --page [4] of cover
Keywords: Deserts -- Juvenile literature; Habitat (Ecology) -- Juvenile literature; Biotic communities -- Juvenile literature; Life zones; Juvenile literature; Desert animals -- Juvenile literature; Desert plants; Juvenile literature; Desert ecology -- Juvenile literature; Ecology